Manajemen Kredit Gadai Sistem Angsuran (KRASIDA) Dalam Meningkatkan Kualitas Pelayanan Pada PT. Pegadaian (PERSERO) UPC Wlingi Kabupaten Blitar - Winarto Winarto; Nik Haryanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Micro, Small and Medium Enterprises (MSMES) engaged in the world of Food and Beverage (F&B) in the Sentul Village area are one of the community service partners. One of these partners was established by the RT 01 association in the Sentul Village area with the lack of a conventional marketing system owned by these MSMEs. By providing various trainings and also providing socialization on the importance of digital marketing so that the marketing system can be improved so that it can cover more business targets and can be a better sales support. MSMES are also provided with service assistance in creating business accounts on digital media such as Instagram, Tiktok, Facebook, and Google Business accounts with optimal digital media management. marketing communication is able to build a brand. In line with the above, marketing communication is an effort to convey messages to the public, especially target consumers, regarding the existence of products in the market, so that they contribute to brand awareness for the company.